Surface Characterization of Atmospheric Pressure Plasma‐Deposited Allyl Methacrylate and Acrylic Acid Based Coatings. Issue 6 (17th April 2013) - Nisol, Bernard; Batan, Abdelkrim; Dabeux, François; Kakaroglou, Alexandros; De Graeve, Iris; Van Assche, Guy; Van Mele, Bruno; Terryn, Herman; Reniers, François
Abstract This work deals with the plasma‐deposition of allyl methacrylate (AMA) and acrylic acid (AA) on metallic substrates. The plasma setup used is an atmospheric pressure radio frequency (RF) torch. Infrared reflection absorption spectroscopy (IRRAS) and X‐ray photoelectron spectroscopy (XPS) are used as characterization tools. In addition, spectroscopic ellipsometry (SE) has been used to control the thickness and calculate the corresponding deposition rates. Whereas the surface chemistry of plasma deposited AMA does not seem to be influenced by the plasma power, acrylic acid based coatings are strongly degraded with the increasing power. AMA seems to allow an efficient polymerization, while at the same time is particularly resistant to plasma induced fragmentation in the range of power used. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>